Identity Branding: Kampoeng Kajoetangan Sebagai Wisata Ikonik Kota Malang - Widodo, Herru Prasetya; Ghofur, Muhammad Abdul; Ince, Alfrida Nona (Unitri Press, 2024)
One of the cities in East Java Province is Malang City, which offers a number of tourist destinations, including Kajoetangan Village, Arema Blue Village, Jodipan Colorful Village, Malang Square, and Malang Monument. Of the many tourist attractions available, Kampoeng Kajoetangan is one of the new tourist attractions that requires identity branding. The purpose of creating identity branding is to introduce these tourist attractions to the wider community or tourists, give them their own identity, and be a differentiator from other tourist attractions. Kampoeng Wisata Heritage Kajoetangan Malang is one of the cultural tourism villages that, with its characteristics, has Dutch architectural houses as well as religious cemeteries and culinary tours. The results of this study indicate that the identity branding of Kampoeng Wisata Heritage Kajoetangan is generally applied to almost all of them. A brand as a product has components that form a brand identity, including attractions, facilities and infrastructure, transportation, culinary, and religious tourism. Brand as organization has several components, including institutions, which include government, pokdarwis, society, and culture. A person's brand has several components, including managers and pokdarwis themselves. Brand as a symbol, which has several components, including a logo, brand name, tagline, and also a brand story. Abstrak Salah satu kota di Provinsi Jawa Timur adalah Kota Malang yang menawarkan sejumlah destinasi wisata, antara lain Kampung Kajoetangan, Kampung Biru Arema, Kampung Warna-Warni Jodipan, Alun-Alun Malang, dan Tugu Malang. Dari sekian banyak tempat wisata yang tersedia, Kampoeng Kajoetangan tersebut merupakan salah satu tempat wisata baru yang membutuhkan adanya branding identitas. Tujuan dari membuat branding identitas tersebut untuk memperkenalkan tempat wisata tersebut ke masyarakat luas atau wisatawan serta mempunyai identitas sendiri dan menjadi pembeda dengan tempat wisata lainnya. Kampoeng Wisata Heritage Kajoetangan Malang merupakan salah satu kampung wisata budaya yang dengan ciri khas mempunyai rumah berarsitektur Belanda dan juga Makam Religi dan wisata Kuliner. Hasil penelitian ini menunjukan bahwa branding identitas Kampoeng Wisata Heritage Kajoetangan pada umumnya hampir diterapkan semuanya. Brand as product memiliki komponen-komponen yang membentuk brand identitas diantaranya atraksi,fasilitas dan infrastruktur, transportasi, kuliner dan wisata religi. Brand as Organization memiliki beberapa komponen diantaranya kelembagaan yang meliputi pemerintah, Pokdarwis dan masyarakat serta budaya. Brand as Person memiliki beberapa komponen juga diantaranya Pengelola dan juga Pokdarwis sendiri. Brand as Symbol yang memiliki beberapa komponen antara lain logo, nama merek, tagline dan juga kisah merek.